Merging entrepreneurial knowledge with science and technology UMK initiaves : a drive to prepare employable graduates - Ahmad Anwar Mohamed Ismail; Aweng Eh Rak; Kassim Buhiran (Faculty of Agro Industry and Natural Resources, Universiti Malaysia Kelantan, 2010)
Universities are seen as the trining ground for production and shaping the minds of our science graduates. These institutions of higher education also provide an impoertant intellectual environment and create the social setting for students to interact, exchange and propound ideas not only for specific cources they chosen to pursue but should also have a good mix with courses that contain commercial and entrepreneurial elements. Universities are expected and must play an additional role. over and above the mundane traditional research and teaching, by embedding into the curriculum entrepreneurial elements in their educational programmes. Entrepreneurial exposure and training should start right at the beginning as the students step into the university and the onus is on the higher education authorities to address the need for producing competent and techno-savvy graduates who are equally competent in entrepreneurial skills. A combination of knowledge on science and technology gained with those on entrepreneurial practices acquired over the period spent in these universities would necessarily equip a graduate for the ever demanding opportunities in the labour market as jobs become more specialized and acute in the private sector. The need to merge entrepreneurship with S&T has to be the way forward to ensure that our graduates become employable either with the public or private sector, but more importantly they could be made to stand on their own two feet as self employed graduates engaging on their own business or enterprise in the ver expanding global market.This paper dwells on the vision, plan of action and strategy of the new kid on the block, Universities Malaysia Kelantan (UMK), which aspires to be unique, different and relevant. The approaches it has taken since its inception in 2007 are highlighted in order to meet and live up to with the university's tagline as an Entrepreneurial Institute of Higher Educational. Strategies are outlined and several approaches discussed on some of the initiatives already taken particularly by the Science and Technology based Faculty of Agro Industry and Natural Resource (FASA)